Photovoltaic panel with bottom-mounted air cooling system - K. Srithar; P. Udhayakumar; M.C. Sundhar; P. Guru Baskar; R. Hemakumar; R. Saravanan (Cleaner Engineering and Technology)
The problem of performance degradation of photovoltaic (PV) panel due to an increase in temperature is analysed in this study and an effort was made to improve it by an active cooling method by placing a set of baffles to enhance the heat transfer. Active cooling is achieved by using an axial fan to cool the rear side of the panel. Two types of baffles that act as turbulence promoters are used in this study. Wavy perforated baffles and trapezoidal perforated baffles are designed based on the requirement for a high Thermal Enhancement Factor and a low friction factor. PV panels with two different configurations of baffles are compared with a conventional PV panel. The mass flow rate of air was varied from 0.28kg/s to 0.67 kg/s to determine the optimum condition of maximum thermal enhancement factor. In comparison with a similar panel without baffles, a set of perforated baffles (WP) increases maximum net power output by 44 %. A Maximum PV panel efficiency of 9.8 % was obtained with WP baffle, as against of 6.8 % for a panel without baffles, for a similar operating condition.